Is Congenital Amusia a Disconnection Syndrome? A Study Combining Tract- and Network-Based Analysis - Wang, Jieqiong; Zhang, Caicai; Wan, Shibiao; Peng, Gang (Frontiers in Human Neuroscience, 2017)
Previous research on congenital amusia mainly focused on the impaired fronto-temporal pathway. It is possible that neural pathways on a larger scale are affected. We investigated changes in structural connections by applying both tract-based and network-based analysis to DTI data of 12 subjects with congenital amusia and 20 demographic-matched normal controls. TBSS (tract-based spatial statistics) was used to detect microstructural changes: the results showed that amusics had higher diffusivity indices in the corpus callosum, the right inferior/superior longitudinal fasciculus, and the right inferior frontal-occipital fasciculus (IFOF). The axial diffusivity values of the right IFOF were negatively correlated with musical scores in the amusia group. Network-based analysis showed that the efficiency of the brain network was reduced in amusics. The impairments of WM tracts were also found to be correlated with reduced network efficiency in amusics. This suggests that impaired WM tracts may lead to the reduced network efficiency seen in amusics. Our findings suggest that congenital amusia is a disconnection syndrome.